Dampak Inovasi Hijau, Energi Terbarukan, Konsumsi Energi terhadap Kinerja Keuangan dan Lingkungan - Riskiana Elina; Nur Hidayah Selviyanti; Slamet Haryono; Imam Buchori (Jurnal Kajian Akuntansi, 2026)
As global pressure for sustainability practices intensifies, many companies face a dilemma between pursuing profitability and fulfilling environmental responsibilities. This study differentiates between pollution prevention and control innovations and explores their impact on Return on Assets (ROA), market value (Tobin's Q), greenhouse gas (GHG) emissions, and the release of hazardous chemicals. The research aims to analyze the effects of green innovation, renewable energy use, and energy consumption levels on the financial and environmental performance of companies listed in the LQ45 index. A quantitative approach using panel data regression analysis is employed. The results indicate that green innovation has a positive and significant effect on financial performance but paradoxically increases environmental burdens due to its still reactive approach. Renewable energy has not yet had a significant financial impact, although it has begun to reduce chemical emissions. Energy consumption correlates positively with financial performance, reflecting suboptimal energy efficiency. These findings highlight the need for more proactive green strategies and efficient integration of renewable energy to achieve long-term sustainability.      Keywords: Green Innovation, Renewable Energy, Energy Consumption, Financial Performance, Environmental Performance